Enhancing Primary School Students' Moral Values Analysis Skills through Gather Town-based Learning Media: A Folk Story Approach - Setiyadi, Ruli; Kuswendi, Uus; Firdaus, Anugrah Ramadhan (PrimaryEdu : Journal of Primary Education, 2024)
This study evaluates the efficacy of employing Gather Town ICT media to enhance elementary school students' analysis skills regarding moral values in folklore. Gather Town is a virtual platform blending gaming and online meeting features, fostering interactive and collaborative experiences. The research adopts a quasi-experimental method with a pretest-posttest control group design, wherein groups are non-randomly assigned. The target population comprises elementary students in Cimahi. Data collection involves a reading skills test assessing students' folklore moral value analysis proficiency across five indicators. Results indicate high scores in various skill areas, including remembering folklore (92.7), interpreting implied meanings (81.3), applying concepts (78.3), analyzing moral values (88.7), and synthesizing folklore (77.3). Hypothesis testing yields a significance value of 0.000, rejecting the null hypothesis. Consequently, Gather Town ICT media proves effective in bolstering elementary students' folklore moral value analysis skills. These findings hold potential for advancing technology-integrated assessment approaches, enhancing evaluation practices in elementary education.